A single-cell view on alga-virus interactions reveals sequential transcriptional programs and infection states - Ku, Chuan (Sci Adv, 2020)
The discovery of giant viruses infecting eukaryotes from diverse ecosystems has revolutionized our understanding of the evolution of viruses and their impact on protist biology, yet knowledge on their replication strategies and transcriptome regulation remains limited. Here, we profile single-cell transcriptomes of the globally distributed microalga Emiliania huxleyi and its specific giant virus during infection. We detected profound heterogeneity in viral transcript levels among individual cells. Clustering single cells based on viral expression profiles enabled reconstruction of the viral transcriptional trajectory. Reordering cells along this path unfolded highly resolved viral genetic programs composed of genes with distinct promoter elements that orchestrate sequential expression. Exploring host transcriptome dynamics across the viral infection states revealed rapid and selective shutdown of protein-encoding nuclear transcripts, while the plastid and mitochondrial transcriptomes persisted into later stages. Single-cell RNA-seq opens a new avenue to unravel the life cycle of giant viruses and their unique hijacking strategies.